Vaginal estrogen therapy and the risk of recurrence in women with a history of breast cancer: Terapia de estrógenos vaginales y riesgo de recurrencia en mujeres con antecedente de cáncer de mama - Boada Fuentes, María Alejandra (2023)
Breast cancer remains the most common malignant neoplasm and one of the leading causes of mortality in women, making it a significant target for global health efforts and a public health priority. Through the use of innovative therapies, survival rates have improved, leading to the emergence of associated conditions such as genitourinary menopausal syndrome. Hormonal therapy is employed for managing this condition, significantly alleviating its symptoms and, in some cases, serving as the sole solution. The most commonly utilized approach is vaginal estrogen therapy. Nevertheless, there have been reports of a potential risk of breast cancer recurrence associated with its use. In the Spanish-speaking context, there is limited evidence discussing this topic. A search was conducted across PubMed, ScienceDirect, and MEDLINE databases, using the terms "Vaginal Estrogen Therapy," "Recurrence," and "Breast Cancer." It was determined that, on a global scale, vaginal estrogen therapy is an effective and safe therapeutic option for managing genitourinary menopausal syndrome in women with a history of breast cancer. This therapy does not appear to increase the risk of recurrence, with the exception of those undergoing treatment with aromatase inhibitors. For these individuals, alternative therapies are recommended to mitigate this potential risk.